Stakeholders' perceptions of the socio-economic and environmental challenges at Lake Victoria - Van den Broek, Karlijn (Lakes & reservoirs, 2019)
Developing policy that is both relevant and supported requires an understanding of stakeholders' account of the key challenges in society. Such insights allow policymakers to better align their policy and collaborate with stakeholders to successfully manage the challenges. To this end, the present study reports on a problem analysis conducted with Lake Victoria stakeholders. A thorough stakeholder mapping procedure was followed by semistructured interviews with businesses, NGOs, governmental organizations and communities. In these interviews, stakeholders discussed what they perceived to be the most pressing challenges in the region, as well as their causes and possible mitigation strategies. The analysis resulted in 12 key challenges raised by the stakeholders that cover socio-economic, environmental, health and institutional issues. Stakeholder analysis revealed that the type of challenges discussed varied across countries and stakeholder institutions. Based on these analyses, the present study concludes that these diverse perceptions must be taken into consideration in future policy formulation and that a strong partnership between policymakers and stakeholders is crucial to mitigate these challenges.
Gesehen am 17.04.2020